Development of attitude competency assessment test based on teaching of Ki Hadjar Dewantara in elementary and secondary school - Yuli Prihatni; Supriyoko Supriyoko; Rahmatang Rahmatang (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
This developmental research aimed to (1) produce an attitude competency assessment model that is standardized based on the teachings of Ki Hadjar Dewantara, (2) Determine the attitude competency assessment indicators in elementary and secondary schools, and (3) Determine the tendency of attitude competency of students in elementary and secondary schools. This research was a type of developmental research. The research was carried out in three provinces in Indonesia, namely DIY (Special Region of Yogyakarta), Central Java, and South Sulawesi. This research conducted in three stages: pre-development, instrument development, and instrument testing. The subject of this study was 497 students in elementary and secondary schools. Content validity was analyzed using the Aiken Index, and construct validity was analyzed using exploratory factor analysis. The findings are (1) the compilation of affective attitude competency assessment models that are standardized based on the teaching of Ki Hadjar Dewantara to realize noble character students. This research has succeeded in establishing attitude competency assessment indicators in elementary and secondary schools, including 6 indicators. (3) The tendency of Ngandel (trust) attitude to students in the subject trial included in the High category, Kendel (brave) Aspect included in the High category, Bandel (naughty) aspects included in the medium category, and Kandel aspect included in the High category.